2021
DOI: 10.3390/s21030877
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Retrieval in Farmland Areas with Sentinel Multi-Source Data Based on Regression Convolutional Neural Networks

Abstract: As an important component of the earth ecosystem, soil moisture monitoring is of great significance in the fields of crop growth monitoring, crop yield estimation, variable irrigation, and other related applications. In order to mitigate or eliminate the impacts of sparse vegetation covers in farmland areas, this study combines multi-source remote sensing data from Sentinel-1 radar and Sentinel-2 optical satellites to quantitatively retrieve soil moisture content. Firstly, a traditional Oh model was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…In recent decades, experiments have demonstrated that CNN-based deep learning methods are reliable for predicting SM using multisource data [46][47][48]63]. Recently, CNNs have been used successfully for SM estimations based on Sentinel multisource data [49].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, experiments have demonstrated that CNN-based deep learning methods are reliable for predicting SM using multisource data [46][47][48]63]. Recently, CNNs have been used successfully for SM estimations based on Sentinel multisource data [49].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…CNNs were originally designed to resolve image classification problems and they have been applied effectively for remote-sensing-based image classification [44][45][46][47][48]. Recently, CNNs have been successfully used for soil moisture estimations based on Sentinel multi-source data [49]. Integrating multiple machine learning methods for rainfall retrieving gains rare attention.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have constructed an NN model based on microwave data for estimating soil moisture [36,37]. Tere is also a synergistic use of microwave and optical data to retrieve soil moisture using NN models [38,39]. In these studies, NN models estimated soil moisture with a high degree of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, using multisource remote sensing data as the input. For example, Liu et al [33] used polarimetric decomposition features and vegetation indexes as the input of GRNN for SM estimation. Zhang et al [31] evaluated the importance of twenty-nine different features to SM estimation using GRNN.…”
Section: Introductionmentioning
confidence: 99%